Penyuluhan Pola Hidup Sehat Pada Anak Usia Dini di PAUDQU Al-Asyary - Sakum; Siti Sopiah; M. Padly; Sarwo Edy; Nenda; MH Ainulyaqin (DPPM Universitas Pelita Bangsa, 2023)
From the results of observing healthy lifestyles and how to brush teeth properly and correctly, there are still many children who do not maintain a healthy lifestyle and healthy teeth, therefore the author provides information on healthy lifestyles and good and correct toothbrushing procedures. A healthy lifestyle and dental health in children will greatly influence the growth and development of their teeth. One of the efforts to maintain a healthy lifestyle and healthy teeth is to provide education on healthy lifestyles and proper and correct toothbrushing procedures. Community service carried out by the author is carrying out counseling on healthy lifestyles and proper and correct toothbrushing procedures at PAUDQU Al-Asyary, West Cikarang, Bekasi. The speakers for this activity are students implementing the program. Participants in this activity are children from classes A and B at PAUDQU Al-Asyary, which aims to increase the knowledge of young children regarding the importance of toothbrushes and good and correct toothbrushing procedures.